Group Counseling with Cognitive Therapy Group and Extinction Techniques to Reduce Academic Procrastination - Puspita, Relegia; Sugiharto, Dwi Yuwono Puji; Sugiyo, Sugiyo (Jurnal Bimbingan Konseling)
Studies related to the use of cognitive therapy group and extinction techniques have happened to be ineffective to reduce academic procrastination, so this study aimed at proofing that the use of group counseling with cognitive therapy group and extinction techniques was effective to reduce academic procrastination. To do so, the researchers employed Randomized Pre-test ? Post-test Comparison Group Design. This design was applied to 14 people chosen randomly based on the pre-test results using academic procrastination scale. These people were divided into two groups. Based on the results of Wilcoxon test, it was known that cognitive therapy group technique was effective to reduce academic procrastination (Z = -2.37; p < 0.05). Similarly, extinction technique was also effective to reduce academic procrastination (Z = -2.36; p < 0.05). In details, extinction technique was more effective than cognitive therapy group in reducing academic procrastination (Z = -5.13; p < 0.05). Thus, these findings contribute implications for counselors. First, the counselors are suggested to use cognitive therapy group and extinction techniques to reduce academic procrastination. Second, the counselors should pay more attention on the processes of group counseling during the implementation.